2016
DOI: 10.1016/j.stem.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Haploid Human Embryonic Stem Cells: Half the Genome, Double the Value

Abstract: Recent advances in the generation of haploid embryonic stem cells (ESCs), capable of self-renewal and differentiation, have laid the groundwork for numerous biomedical applications in developmental biology and reproductive medicine. When combined with the power of genetic screening, haploid human ESCs could advance cancer research, regenerative medicine, and disease modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…1A). This observation is consistent with previous studies using haploid cells that have linked this action to the "diploidization" of the haploids (19). To specifically analyze the growth properties of haploid HAP1 cells, haploid and diploid cell populations were FACS-sorted and grown independently.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1A). This observation is consistent with previous studies using haploid cells that have linked this action to the "diploidization" of the haploids (19). To specifically analyze the growth properties of haploid HAP1 cells, haploid and diploid cell populations were FACS-sorted and grown independently.…”
Section: Resultssupporting
confidence: 88%
“…Although this phenomenon has been considered a consequence of diploidization (19), here we have shown that it is due to reduced fitness and growth properties of haploid cells, which are outcompeted by the diploid cells existing in these cultures. At least in mammals, this reduced fitness is explained in part by the activation of a p53-dependent cytotoxic response, associated with difficulties arising during the segregation of haploid DNA content.…”
Section: Discussionmentioning
confidence: 60%
“…Data on essential genes in haploid hESCs was obtained from Yilmaz et al (Yilmaz et al 2016); data on essential genes in human cancer cell lines was obtained from Yusa et al (Tzelepis et al 2016) and Wang et al (Wang et al 2017). Genes essential only in ESCs were defined as genes essential in mESCs and hESCs (FDR corrected P < 0.05) but not essential in more than one of the 11 human cancer cell lines.…”
Section: Comparison Of Essential Genes Between Mescs Hescs and Cancementioning
confidence: 99%
“…Aside from the value of haploid human ESCs in understanding human development, they may also play a role in future procedures of reproductive medicine, providing a putative source for haploid gametes. Yet, the most obvious usefulness of haploid human ESCs is in the context of haploid genetics, enabling simplified loss-of-function screening on a human genetic background (for a broader view on the biomedical applications of haploid human ESCs, see Yilmaz et al, 2016). We anticipate that haploid human ESCs will serve as useful tools for studying human genetics, development, and pathology in a wide range of research fields.…”
Section: Discussionmentioning
confidence: 99%